Strukturalisme Roman Ingarden Dalam Lirik Lagu Dalam Hitungan, Tarian Penghancur Raya, Peradaban Karya .Feast: Kajian Sosiologi Sastra - Amai Nauli Saragih; Nurhayati Harahap; Amhar Kudadiri (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study aims to analyze the social critique embedded in the lyrics of the songs “Dalam Hitungan,” “Tarian Penghancur Raya,” and “Peradaban” by the band .Feast. These songs were selected because they contain elements of social criticism that reflect the societal realities. The research uses a literary sociology approach with two main theories: Strata Norma Roman Ingarden theory which consists of five strata (layers) of norms: the sound layer, the meaning layer, the object layer, the world layer, and the metaphysical layer to analyze the structural elements of the song lyrics , and Georg Lukács’ socialist realism theory to explore the social critique embedded within the lyrics. The research method employed is library research with a qualitative descriptive analysis, where data is obtained from the song lyrics and analyzed using the relevant theories. The findings indicate that these three songs critique various social issues such as materialism, the technological advancement that erodes spiritual values, and the injustices occurring in society. The social critique expressed through the lyrics is not only explicit but also reflected in the symbolism of sound and the deep use of language. This study is expected to contribute to the development of literary studies, especially in understanding how musical works, particularly song lyrics, can serve as effective media for social critique. Furthermore, this research reveals the relevance of literary sociology in analyzing art that contains critiques of social phenomena.